KUALITAS PELAYANAN PUBLIK - Harius Eko Saputro (Professional: Jurnal Komunikasi dan Administrasi Publik, 2015)
Service is the main task of the state apparatus. The scope of services and public services covered broad aspects of community life. This task has been clearly outlined in the preamble of the 1945 Constitution that is in the fourth paragraph. In practice, public services in Indonesia have not been going well. The provision of public services by government officials to the public is actually an implication of the state apparatus functions as a public servant. Therefore, the position of the government apparatus in public services is very strategic because it will determine the extent to which the government is able to provide the best possible service to the community, which thus will determine the extent to which the state has to perform its role properly in accordance with the purpose of founding. The indicator of public services quality are punctuality, ease of filing, the accuracy of error-free services, and service charges. It is highly influenced by the organizational structure, the ability of the apparatus and service systems. Keywords: Public, Service, Quality